Let Them Eat Beef:: The Prince Edward Island-Newfoundland Beef-Cattle Trade, 1942-1946 - Slumkoski, Corey (Acadiensis, 2006)
Abstract This paper highlights the difficulties faced by small provinces in the Canadian federation by examining the efforts of Premier Walter Jones of Prince Edward Island to develop his province's live beef-cattle trade with Newfoundland during the 1940s. Although Prince Edward Island was well placed to meet the escalating demand for beef in Newfoundland during the Second World War, the lack of shipping capacity proved to be a major problem. Even when subsidized shipping was secured, it ignored pre-existing, inter-island trade relationships and, as a result, central Canadian shipping interests benefited as much from Ottawa's decisions as did Prince Edward Island cattle producers.